2021
DOI: 10.3389/fbuil.2021.767779
|View full text |Cite
|
Sign up to set email alerts
|

Resilient Communities: A Novel Workflow

Abstract: This study presents a novel workflow to define how resilient communities can be analysed and improved through the optimisation of sustainable design principles through quantitative methods. Our model analyses successful sustainable communities extracting information about daily routines (commuting, working, use of buildings etc.). From these routines, we infer a set of key successful aspects based on location, density and proximity. We then model a resilient community and analyse it using a combination of clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…The satellite images from the first dataset (all of which were at the same altitude and resolution) have been labelled one by one using Microsoft VoTT: Visual Object Tagging Tool (Microsoft, 2019). Our previous work on the city of Copenhagen (Carta et al, 2021) showed that resilience values calculated on proximity and density of physical elements are mostly affected by green areas, natural elements and entertainment venues. Based on these previous findings, we focused on the 4 visually recognisable typologies below to identify relevant classes for our training: 1) Green areas, 2) Buildings (built areas vs unbuilt), 3) Large infrastructures (train stations, stadiums etc.)…”
Section: Data Preparation and Labellingmentioning
confidence: 99%
See 3 more Smart Citations
“…The satellite images from the first dataset (all of which were at the same altitude and resolution) have been labelled one by one using Microsoft VoTT: Visual Object Tagging Tool (Microsoft, 2019). Our previous work on the city of Copenhagen (Carta et al, 2021) showed that resilience values calculated on proximity and density of physical elements are mostly affected by green areas, natural elements and entertainment venues. Based on these previous findings, we focused on the 4 visually recognisable typologies below to identify relevant classes for our training: 1) Green areas, 2) Buildings (built areas vs unbuilt), 3) Large infrastructures (train stations, stadiums etc.)…”
Section: Data Preparation and Labellingmentioning
confidence: 99%
“…Firstly, we used data from existing literate and rankings, using data from the 2013 Grosvenor report (Barkham et al, 2013) and the Quality of Life global ranking from Numbeo (2021). Secondly, we evaluate the resilience values for the same cities using the method we developed in previous work (Carta et al, 2021), as detailed in Section 3.1. We then compared the three sets of values to estimate the precision of our model.…”
Section: Model Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous work (Carta et al, 2021), we developed a quantitative method to evaluate the resilience of net-zero communities, based on position, density and proximity of physical resources. In this paper we present further findings where we apply our method to generate an online tool to automatically evaluate the level of resilience of any neighbour and urban area based on their urban configuration.…”
Section: Introductionmentioning
confidence: 99%